Occurrences of mild compression wood in agathis borneensis and dacrydium elatum - Yoon, Soo Kim; Kwang, Ho Lee; Wong, Andrew H.H (Koninklijke Brill NV, Leiden, 2015)
Studies on the compression wood in tropical gymnosperms are uncommon due to their limited distribution and over-exploitation. Microscopic examination of the heartwood of two tropical gymnosperms, Agathis borneensis (local name: bindang, damar minyak) and Dacrydium elatum (local name: sempilor) growing on higher elevations in Sarawak, Malaysia showed the occurrence of mild compression wood. Intercellular spaces were present in the compression wood of A. borneensis, but not in D. elatum. Rounded shapes of tracheids, typical of severe compression wood, were not observed in any of the samples examined. In D. elatum helical cavities were present, which corresponded in location to cell wall checks seen in cross-sectional views. The S1 layer was relatively thick in both wood species but a distinct S3 layer was observable only in the mild compression wood of D. elatum. Although the main feature of the mild compression wood tracheids of both wood species was greater lignification of the outer S2 region, autofluorescence and KMnO4 staining showed the fluorescence and staining intensity in the corner middle lamella in some cases to be much stronger than that in the outer part of S2 layer.